Peran Pembina Kursus Mahir Lanjutan yang Dipengaruhi Faktor Pelatihan, Motivasi Pembina, dan Fasilitas Kegiatan di Lingkungan Kwarcab Pramuka Kabupaten Pidie Jaya - Zulfikar Zulfikar; Mai Simahatie; Novida Humaira (Singkite Journal, 2026)
The role of the Scout Leader is part of the cycle of fostering and protecting Scout members. The quality of this role is greatly enhanced by training, motivation, and facilities for the activities they undertake. Many obstacles remain in implementing the role of Scout Leader in the Pidie Jaya Regency Scout Branch. Therefore, this study attempts to examine this through a case study of Advanced Course activities. Survey methods, quantitative associative research, and inferential statistical analysis using a path model were used. The results show: (1) training, motivation, and facilities are causally interconnected, with a strong correlation, directly and indirectly influencing the role of Scout Leader. The role of Advanced Course Instructor is influenced by training by 33.3%, by Scout Leader motivation by 22.01%, and by Activity Facilities by 34.47%. (2) Together, the elements of training, motivation, and activity facilities contribute positively by 84.1% to the role of Advanced Course Instructor in the Pidie Jaya Regency Scout Branch.